Learning and Study Skills in Students at a Small Liberal Arts College (European Journal of Teaching and Education, 2024)
Despite a large body of literature on the various study skills that predict academic performance in college students, there is no consensus on which specific study skills contribute the most toward college success. Additionally, the emphasis in the literature is primarily on large public universities and specialized groups such as chiropractic, medical, pharmacy, and vocational students, with little to no research focused on small liberal arts institutions. Finally, studies in the field typically assess all students, and use a wide range of GPAs in examining differences between high- and low-performing students. It is important to see if differences in study strategies exist even when only a small subset of students are tested – many of whom are on probation for already low academic performances. The present study assessed ten different learning and study skills via the Learning and Study Skills Inventory (LASSI) in 41 students enrolled in a general studies class at a small liberal arts college. Academic achievement was assessed via cumulative GPA for each student. There were significant correlations between individual scores on the motivation subscale and GPA, and between utilizing academic resources and GPA. Both motivation and utilizing academic resources were found to also significantly predict GPA. Theoretical and practical implications of these findings are discussed, in the context of enhancing student success via early and proactive interventions.